Sports Massage for Athletes : SMA Keberbakatan Olahraga at North Sulawesi - Yudha Rello Pambudi; Muh. Khafid Ansori; Hasnur Aginta Hasnur; Agung Rahmat; Jihan Apande; A. Nurmutmainnah (STAI Nurul Islam Mojokerto, 2026)
This community service activity aims to improve the basic knowledge of students and athletes at the State High School for Sports Talent (SMANKOR) of North Sulawesi Province about sports massage and sports injury management. The method used was a pre-experimental with a one-group pre-test and post-test design. A total of 55 active students were selected using a total sampling technique as activity participants. The intervention was carried out on May 12, 2026, through a combination of presentations, demonstrations, and direct practice. The results of the Wilcoxon Signed Rank Test showed a Z value = −5.504 with Asymp. Sig. = 0.000 (p less than 0.05), which proved there was a significant increase in knowledge after the intervention. The average value increased from 6.96 (pre-test) to 8.49 (post-test), accompanied by a decrease in the standard deviation from 1.732 to 0.979, which indicated an even distribution of understanding among participants. It was concluded that structured sports massage education effectively improves students'/athletes' cognitive knowledge and needs to be integrated into the sports-based school physical education curriculum.